2020
DOI: 10.1038/s41598-020-73939-8
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of climate change and human activities on the water discharge and sediment load of the Pearl River, southern China

Abstract: Global climate change and human activities have important effects on the water discharge and sediment load of the Pearl River. In this study, the water discharge and sediment load were investigated by using hydro-meteorological data from 1954 to 2018. The linear regression, Mann–Kendall abrupt test and double mass curve were employed to detect trends and abrupt change-points in water discharge and sediment load and to quantify the effects of climate change and human activities on water discharge and sediment l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…However, the sediment load exhibited a significant decreasing trend since the 1990s, regardless of the water discharge. Dam construction in the drainage basin is the main reason for the drastic reduction in sediment load 20 , 22 , 23 , 37 . Statistics indicate that over 9000 dams and reservoirs have been constructed in the Pearl River Basin since the 1950s.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the sediment load exhibited a significant decreasing trend since the 1990s, regardless of the water discharge. Dam construction in the drainage basin is the main reason for the drastic reduction in sediment load 20 , 22 , 23 , 37 . Statistics indicate that over 9000 dams and reservoirs have been constructed in the Pearl River Basin since the 1950s.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that LD, the largest dam in the Pearl River Basin, was constructed in 2006 with a storage capacity of 29.9 × 10 9 m 3 . According to the Mann–Kendall test analysis, Wei et al (2020) suggested that the abrupt change in sediment load during this period occurred in 1998 23 . The linear regression equations for annual sediment load suggest a decrease of 178 × 10 4 t/year from 1998 to 2018.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Damaging hydrological events triggered by either short and intense storms, or longer duration rainfall (e.g., Diodato et al, 2020b;Duulatov et al, 2021), cause sustained erosive forcing and considerable soil losses in many parts of the world (Wuepper et al, 2020). They may increase in frequency and/or severity with changes in the climate system associated with global warming (Easterling et al, 2000;Morera et al, 2017;Harris et al, 2018;Rineau et al, 2019;Wei et al, 2020). Understanding the dynamics and current developments of climate extremes (e.g., Garcia-Herrera et al, 2014) with rainfall erosivity pose significant challenges for quantifying their impact on landscapes.…”
Section: Introductionmentioning
confidence: 99%
“…The water quality management and biodiversity protection functions are strongly affected by the hydrological exchange flows (Harvey, 2016) that are driven by hydrostatic pressure and flow-sediment induced dynamic pressure (Tonina and Buffington, 2007;Cardenas and Wilson, 2007). As the magnitude, frequency, and peak time of discharge are projected to vary with future climate and anthropogenic conditions (Potter et al, 2004;Veldkamp et al, 2018;Wei et al, 2020;Xu et al, 2021), it is essential to establish a numerical modeling framework that enables evaluating and predicting the impact of climate-or human-induced discharge variations on streamflow and river functions.…”
Section: Introductionmentioning
confidence: 99%